Pola Kemitraan Jaringan Sosial Swadiri Bali (JSSB) dengan Petani (Bina Karya Mandiri) dalam Penyaluran Bantuan dari Pemerintah - K REDIK MARDIKA; I WAYAN WINDIA; NYOMAN PARINING (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
The Partnership Pattern of the Bali Self-Social Network ‘Jaringan Sosial SwadiriBali’ (JSSB) and Farmers (Bina Karya Mandiri) in the Distribution of the Grant Provided by the Government The government provides different types of grant to the farmers; however, this does notmean that the farmers always have immediate access to them. There are manyrequirements which should be fulfilled by the farmers. The Bali Self-Social Network‘Jaringan Sosial Swadiri Bali (JSSB) helps the group of farmers referred to as BinaKarya Mandiri obtain the grant provided by the government through the pattern ofpartnership. This current study was intended to identify the mechanism, the rights andobligations, and the obstructions which the partnership between JSSB and the farmers(Bina KaryaMandiri) faces in the distribution of the grant provided by the government.The samples of the current study were determined using the sampling purposivetechnique. The data were collected through in-depth interview, rapid rural appraisal,library research and documentary methods. Then the data were qualitatively analyzed. Itcould be concluded from the study that JSSB prepares production facilities, productiontechnological guidance and supervision as to where to market the products and BinaKarya Mandiri prepares land and manpower to support the production process. In thepartnership JSSB is not entitled to the benefit obtained by Bina Karya Mandiri;however, it is entitled to supervising the activities done byBina Karya Mandiri. Bina Karya Mandiri is entitled to having the production facilities fixed, and Bina KaryaMandiri is obliged to report the development of the group every month. The problem isthat the group’s members are getting less interested in doing the group’s activities. Itwill be better if the group’s members maintain the partnership between Bina KaryaMandiri and JSSB as it benefits them.